The Facts on File dictionary of biology - Tootill, Elizabeth; Facts on File, Inc. (New York Facts On File Publications, 1988)
A reference tool for professional and student biologists spans everything from abaxial to zymogen granules, explaining such biological phenomena as photosynthesis, regeneration, and cytoplasmic inheritance.
Keywords: Biology -- Dictionaries